Link Adaptation Algorithm for IEEE 802.11 Wireless Local Area Netwoks in Fading Channel - Wan Norsyafizan W Muhamad; Suzi Seroja Sarnin; Azlina Idris; Aliya Syahira (Institute of Advanced Engineering and Science, 2018)
This paper proposes an enhance version of the dual parameter based cost function algorithm for time-varying environments. For ideal channel condition, the proposed cost function algorithm adaptively change the transmission data rate according to traffic load condition. However, similar approach is not well-suited for time-varying environment. For time-varying condition, transmission of packet at lower transmission data rate is much preferred in order to achieve reliable transmission. In addition to that, packet transmission at lower data rate contributes to low energy consumption due to lower transmit power used to transmit packet. This paper presents a combination of cost function algorithm with adaptive rate/power. Adaptation of transmission data rate and transmit power for time varying condition are carried out based on received power values. An OPNET based simulation model was developed to analyses the performance of the propose algorithm. Simulation results show the proposed algorithm can significantly improve the energy efficiency of a WLAN while maintaining the network QoS in fading channel environments.